Glycohemoglobin A1c: A promising screening tool in gestational diabetes mellitus - Aldasouqi, Saleh A. (Medknow Publications, 2008)
CONTEXT: Current screening tests for gestational diabetes mellitus (GDM) are inconvenient. Therefore, alternative screening tests for GDM are desirable. The use of glycohemoglobin A1c (HbA1c) in screening for GDM remains controversial. AIM: We undertook this study to evaluate the utility of HbA1c in screening for GDM. SETTINGS AND DESIGN: Retrospective study in a tertiary teaching hospital. MATERIALS AND METHODS: Laboratory records were reviewed to identify pregnant women who underwent both oral glucose tolerance test (OGTT) and HbA1c measurements over a 16-months period. The association of OGTT with HbA1c was evaluated. STATISTICAL ANALYSIS USED: Data were collected using SPSS software. Comparisons of the means and calculations of sensitivities were performed. RESULTS: Of 145 eligible patients, 124 had GDM and 21 patients did not, per OGTT. The percentages of patients with HbA1c values (reference range of 4.8%–6.0%) equal to or above sequential cut-point values of 5.0%, 5.5%, 6.0%, 6.5% and 7.0% (i.e., sensitivity values) were 100%, 98.4%, 87.1%, 62.9% and 39.5%, respectively. The mean HbA1c of the patients with GDM was 6.9 + 0.8% compared to 6.4 + 0.6% for those without GDM (P< 0.006). At an arbitrary cut-off value of 6.0% (the upper limit of normal), HbA1c would have picked up 87.1% of patients with GDM. CONCLUSIONS: This study suggests that HbA1c is a reasonably sensitive screening measure of GDM in this high-risk population. Acknowledging limitations resulting from the study design, further prospective studies are warranted to verify this conclusion, and to evaluate the specificity of HbA1c as a screening test for GDM.